1999
DOI: 10.1002/(sici)1097-0231(19990715)13:13<1231::aid-rcm579>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Routine analysis by high precision gas chromatography/mass selective detector/isotope ratio mass spectrometry to 0.1 parts per mil

Abstract: Stable isotope methods are potentially quite useful for validating natural or enhanced mineral degradation of contaminants. For this reason, a continuous flow gas chromatograph (GC), isotope ratio mass spectrometer (IRMS) has been coupled with a quadrupole mass selective detector (MSD) to allow simultaneous mass spectral and stable carbon isotope ratio data to be obtained from a single chromatographic analysis. This allows the target contaminant and any extra-cellular degradation intermediates to be both quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…An even better separation could be achieved using a lower GC temperature, however, this also results in a stronger separation of the CO 2 isotopologues, thus, increasing the time shift between m/z 44 and m/z 45 (Meier-Augenstein et al, 1996). Although this time shift can be accounted for by the software, we observed a stronger dependence of the isotopic ratio on the amount of the sample (usually referred to as linearity effects or amount dependency), a common phenomenon with GC-IRMS applications (Hall et al, 1999;Schmitt et al, 2003). Therefore, we choose a GC temperature of 110 • C, which results in a sufficient separation between CO 2 and N 2 O of 14 s (see Fig.…”
Section: Cryofocus Gc Irms Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…An even better separation could be achieved using a lower GC temperature, however, this also results in a stronger separation of the CO 2 isotopologues, thus, increasing the time shift between m/z 44 and m/z 45 (Meier-Augenstein et al, 1996). Although this time shift can be accounted for by the software, we observed a stronger dependence of the isotopic ratio on the amount of the sample (usually referred to as linearity effects or amount dependency), a common phenomenon with GC-IRMS applications (Hall et al, 1999;Schmitt et al, 2003). Therefore, we choose a GC temperature of 110 • C, which results in a sufficient separation between CO 2 and N 2 O of 14 s (see Fig.…”
Section: Cryofocus Gc Irms Injectionmentioning
confidence: 99%
“…Typically, the drift is on the order of 0.04 ‰ h −1 . After this trend correction, the area-δ 13 C relationship from three different peak sizes (L1, L2, L3) is calculated and all measured peaks are corrected for "linearity" effects (Hall et al, 1999;Schmitt et al, 2003). The typical slope of the area-δ 13 C function is 0.002 ‰ Vs −1 .…”
Section: Correctionsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] While fractionation effects during derivatization have been investigated at least theoretically, 9 the dependence of the isotopic signal on variations in amounts of substance when using a GC-C-IRMS has attracted less attention. As pointed out by Hall et al 10 and by Glaser and Amelung 5 , d 13 C-values of individual compounds such as alkanes and amino acid enantiomers may depend on the sample amount injected. Meier-Augenstein et al 11 found that even minute chromatographic changes, such as temperature gradients, alter the isotopic compositions derived for the peaks.…”
mentioning
confidence: 90%
“…Generally, the term non-linearity is used to describe this effect. 12,13 In this paper we follow the suggestion of Hall et al 10 and use amount dependence, since 'linearity' usually describes a 1st order polynomial function. Up to now, this undesired drift with signal size 4 has been corrected using logarithmic functions that reflect changes in d 13 C upon the injection of different amounts of standards.…”
mentioning
confidence: 99%
See 1 more Smart Citation